TINJAUAN YURIDIS MENGENAI KEABSAHAN PERJANJIAN DIBAWAH TANGAN DITINJAU DARI PASAL 1875 KITAB UNDANG-UNDANG HUKUM PERDATA (Studi Putusan Pengadilan Negeri Singaraja Nomor Perkara 462/Pdt.G/2015/PN.Sgr) - Ni Kadek Erlina Dinda Putri; Si Ngurah Ardhya; Muhamad Jodi Setianto (Jurnal Ilmu Hukum Sui Generis, 2023)
This research aims to determine 1) the legal validity of private agreements in cases of default in debt and receivable agreements and 2) the factors that cause default in cases 462/pdt.g/2015/pn.sgr. The type of research that will be used in this writing is normative juridical research. The data source obtained in this research is a secondary data source consisting of primary and secondary legal materials. The research results obtained are 1) the legal validity of private agreements in decision 462/Pdt.G/2015/PN. Sgr, that is, the private agreement is legally valid, where in this case it refers to Article 1875 of the Civil Code, a private writing which is recognized as true by the person who is confronted with it, where in this case the private agreement made is acknowledged by the Plaintiff with evidence in the form of photocopy of the agreement letter under hand made by both parties which has been sufficiently stamped and in accordance with the original and evidence of the facts of the trial from witnesses on behalf of Ketut Suweken and Ketut Sri Diarni who confirmed the agreement, as well as the defendant who did not deny or provide a rebuttal to the plaintiff's claim. proven by the defendant never appearing before the trial. 2) The judge's consideration in Decision 462/Pdt.G/2015/PN.Sgr is that it has explained the reasons for granting the plaintiff's lawsuit in part with verstek which was caused by the defendant's absence from court so that the defendant did not convey his objection to the lawsuit submitted by the plaintiff. As a result of this, it is stated that the defendant legally owes the plaintiff a debt and punishes the plaintiff to pay the debt to the plaintiff with debt compensation of 0.8 percent of the amount of money borrowed and if the defendant is negligent then the activity of selling the collateral will be carried out in public.